2020
DOI: 10.3390/metabo10100388
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Docosahexaenoic Acid and Eicosapentaenoic Acid Concentrations Are Positively Associated with Brown Adipose Tissue Activity in Humans

Abstract: Brown adipose tissue (BAT) activation is a possible therapeutic strategy to increase energy expenditure and improve metabolic homeostasis in obesity. Recent studies have revealed novel interactions between BAT and circulating lipid species—in particular, the non-esterified fatty acid (NEFA) and oxylipin lipid classes. This study aimed to identify individual lipid species that may be associated with cold-stimulated BAT activity in humans. A panel of 44 NEFA and 41 oxylipin species were measured using mass-spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
0
12
1
Order By: Relevance
“…In this context, a recent study in human adipose tissue has revealed that the presence of active BAT is positively associated with an anti‐inflammatory oxylipins/eicosanoids profile 70 . Similarly, EPA and DHA have been recently associated with the levels of BAT activity in humans 71 . A lipidomic analysis of BAT in young mice showed that phospholipids and free fatty acids were more abundant in BAT than in WAT, and that phospholipids in BAT were mostly composed of PUFAs, especially DHA 72 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this context, a recent study in human adipose tissue has revealed that the presence of active BAT is positively associated with an anti‐inflammatory oxylipins/eicosanoids profile 70 . Similarly, EPA and DHA have been recently associated with the levels of BAT activity in humans 71 . A lipidomic analysis of BAT in young mice showed that phospholipids and free fatty acids were more abundant in BAT than in WAT, and that phospholipids in BAT were mostly composed of PUFAs, especially DHA 72 …”
Section: Discussionmentioning
confidence: 98%
“…70 Similarly, EPA and DHA have been recently associated with the levels of BAT activity in humans. 71 A lipidomic analysis of BAT in young mice showed that phospholipids and free fatty acids were more abundant in BAT than in WAT, and that phospholipids in BAT were mostly composed of PUFAs, especially DHA. 72 Our study shows that chronic dietary supplementation with DHA was able to reverse the drop in the sum of SPMs observed in BAT of aged DIO mice, reaching even values significantly higher than those found in BAT of young mice.…”
Section: Discussionmentioning
confidence: 99%
“…Some epigenetic factors could also underlie the activation of BAT by omega-3 [ 190 ]. In humans there are conflicting results that showed a reduction in waist circumference and accumulation of adipose tissue during growth, but the mechanism remains unclear [ 205 ]. NEFAs could be possible biomarkers of BAT activity [ 206 ], but several humans studies are needed to fully elucidate associations between BAT and NEFAs circulating levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, associations between BAT and circulating levels of certain lipid species (classes of non-esterified fatty acids, NEFAs, and oxylipin lipids) have been identified in mice [ 205 ]. In humans, a decrease in weight gain and an increase in BAT activity following high dietary omega-3 intake (from fish or fish oil supplementation recorded by validated semiquantitative food frequency questionnaire) has been observed only in genetically driven, high-number cohort studies and not in clinical trials [ 206 ].…”
Section: Studies On Functional Nutrients On Bat: the Role Of Omega-3 Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation